O Congresso Nacional e sua participação no combate às atividades ilícitas no Brasil (1988 2010) - Pires, Mônica Sodré (2012)
This study aims to map and analyze the actions and behavior of the Brazilian government and National Congress fighting illegal practices from International acts and domestic legal provisions on the subject. To do so, considering the subject area here classified as "illicit" and the period between 06/10/1988 and 31/12/2010, we take as empirical material, on the one hand, the International acts negotiated by the Executive and approved by the Brazilian National Congress with emphasis on the United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances; United Nations Convention Against Corruption and United Nations Convention Against Transnational Organized Crime, known respectively as the Vienna, Merida and Palermo Conventions. On the other hand, we take the ordinary laws in the country, with emphasis on the Law nº 9.613 of 1998, Law nº 9.034 of 1995 and Law nº 10.763 of 2003, known respectively as the Law on Money Laundering, Law on Organized Crime and Law on Corruption. We start from the assumption that systemic international activities, and more specifically the International Regimes, were the main factors behind this government action in combating such practices. We conclude that, in most cases, the relationship between the Powers happens in the form of cooperation and that, contrary to common knowledge that attributes the Legislature with lack of interest and delay in certain subjects, the Representatives and Senators are more active than one might initially assume.